A Framework for Maintaining a Fully Operational Autopsy Service at a Large Academic Teaching Institution During a Global Pandemic - Lucy Fu MD, MSc; Taylor Zak MD, PhD; Elisheva Shanes MD (Elsevier, 2021)
The COVID-19 pandemic created new challenges in health care, and pathology departments have led with innovations in testing and education. While the medical community and public showed great interest in gross and histologic findings in COVID-affected patients, paradoxically many autopsy services nationwide closed due to uncertainties surrounding the proximity to infected patient tissue, shortages in personal protective equipment, and pressures to discontinue perceived nonessential hospital operations. These disruptions furthermore negatively impacted pathology trainee education. The autopsy division at Northwestern Memorial Hospital, with the belief that a fully functioning autopsy service is especially crucial at this time, adopted a framework for continuing at full capacity for both clinical care and education. New operations were modeled on national protocols by the Centers for Disease Control and Prevention and the College of American Pathologists, and the service continually adjusted policies to reflect rapidly changing guidelines and feedback from trainees and staff. Between January and December 2020, we performed 182 adult autopsies including 45 COVID-19 autopsies. Twelve residents, 4 staff, and 5 attendings rotated through the service. In exit interviews, participants expressed: (1) improved comfort managing both COVID-related and general autopsies; (2) sense of personal safety on service (despite the increased risk of exposure); (3) belief that both COVID-related and general autopsies contributed to their personal education and to the medical community. There have been zero known autopsy-related COVID-19 infections to date. We hope that our innovative autopsy service restructuring can serve as a framework for other academic programs during the current and in future pandemics.